A. \(M + m = 63\)
B. \(M + m = 48\)
C. \(M + m = 50\)
D. \(M + m = 41\)
B
Ta có phương trình đường tròn \(\left( C \right):{\left( {x - 4} \right)^2} + {\left( {y - 3} \right)^2} = 9\)
Do điểm A nằm trên đường tròn (C) nên ta có \({\left( {a - 4} \right)^2} + {\left( {b - 3} \right)^2} = 9\)
Mặt khác \(F = 4a + 3b - 1 = 4\left( {a - 4} \right) + 3\left( {b - 3} \right) + 24\)
\(F - 24 = 4\left( {a - 4} \right) + 3\left( {b - 3} \right)\)
Ta có \({\left[ {4\left( {a - 4} \right) + 3\left( {b - 3} \right)} \right]^2} \le \left( {{4^2} + {3^2}} \right)\left[ {{{\left( {a - 4} \right)}^2} + {{\left( {b - 3} \right)}^2}} \right] = 25.9 = 255\)
\( \Rightarrow - 15 \le 4\left( {a - 4} \right) + 3\left( {b - 3} \right) \le 15 \Leftrightarrow - 15 \le F - 24 \le 15 \Leftrightarrow 9 \le F \le 39\)
Khi đó \(M = 39,\,\,\,m = 9\)
Vậy \(M + m = 48\)
Cách 2:
Ta có \(F = 4a + 3b - 1 \Rightarrow a = \frac{{F + 1 - 3b}}{4}\)
\({\left( {a - 4} \right)^2} + {\left( {b - 3} \right)^2} = 9 \Rightarrow {\left( {\frac{{F + 1 - 3b}}{4} - 4} \right)^2} + {b^2} - 6b + 9 = 9\)
\( \Leftrightarrow 25{b^2} - 2\left( {3F + 3} \right)b + {F^2} + 225 = 0\)
\(\Delta ' = {\left( {3F + 3} \right)^2} - 25{F^2} - 5625\)
\(\Delta ' \ge 0 \Leftrightarrow - 16{F^2} + 18F - 5625 \ge 0 \Leftrightarrow 9 \le F \le 39\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247